Biosynthesis and beneficial effects of microbial gibberellins on crops for sustainable agriculture - Keswani, Chetan; Singh, Satyendra P.; García‐Estrada, Carlos; Mezaache‐Aichour, Samia; Glare, Travis R.; Borriss, Rainer; Rajput, Vishnu D.; Minkina, Tatiana M.; Ortiz, Aurelio; Sansinenea, Estibaliz (Journal of applied microbiology, 2022)
Soil microbes promote plant growth through several mechanisms such as secretion of chemical compounds including plant growth hormones. Among the phytohormones, auxins, ethylene, cytokinins, abscisic acid and gibberellins are the best understood compounds. Gibberellins were first isolated in 1935 from the fungus Gibberella fujikuroi and are synthesized by several soil microbes. The effect of gibberellins on plant growth and development has been studied, as has the biosynthesis pathways, enzymes, genes and their regulation. This review revisits the history of gibberellin research highlighting microbial gibberellins and their effects on plant health with an emphasis on the early discoveries and current advances that can find vital applications in agricultural practices.